Fundamentals of advertisement and promotion of Bangladeshi online businesses: observations at Rectangle Communications Ltd. - Shahnewaz, Ahmed Abid (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.